Smoking in Latin America: a major public health problem - Costa e Silva Vera Luiza da; Koifman Sergio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Smoking has become a major public health problem in Latin America, and its scope varies from country to country. Despite difficulties in obtaining methodologically consistent data for the region, we analyzed the results from prevalence surveys in 14 Latin American countries. Smoking prevalence among men varied from 24.1% (Paraguay) to 66.3% (Dominican Republic) and among women from 5.5% (Paraguay) to 26,6% (Uruguay). By applying point prevalence data to the stage model of the tobacco epidemic in developed countries, we concluded that the Latin American countries are in stage 2, i.e., with a clearly rising prevalence among men, a prevalence for women that is beginning to increase, and mortality attributable to smoking among men still not reflecting peak prevalence. None of the countries analyzed appeared to have reached stage 3, in which one observes a downward trend in prevalence of smoking among men and peak prevalence among women, with broad impact on tobacco-related mortality. The only exception appears to be Paraguay, which is still emerging from stage 1, i.e., with low prevalence rates among men, too. Nevertheless, high lung cancer mortality rates in Uruguay and Argentina are comparable to those of the developed countries.